2017
DOI: 10.1016/j.scitotenv.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Tracking cyanobacteria blooms: Do different monitoring approaches tell the same story?

Abstract: Cyanobacteria blooms are a major environmental issue worldwide. Our understanding of the biophysical processes driving cyanobacterial proliferation and the ability to develop predictive models that inform resource managers and policy makers rely upon the accurate characterization of bloom dynamics. Models quantifying relationships between bloom severity and environmental drivers are often calibrated to an individual set of bloom observations, and few studies have assessed whether differences among observing pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 119 publications
0
27
0
Order By: Relevance
“…Lower streamflows occur during periods with high evapotranspiration and less turbulent waters, conditions conducive to cyanobacterial dominance. Bertani et al ( 2017 ) found a negative relation between bloom size and streamflow and suggested this was consistent with cyanobacterial growth being favored by lower summer flushing rates and higher residence time. In the current study, a seasonable variable was used in three models.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Lower streamflows occur during periods with high evapotranspiration and less turbulent waters, conditions conducive to cyanobacterial dominance. Bertani et al ( 2017 ) found a negative relation between bloom size and streamflow and suggested this was consistent with cyanobacterial growth being favored by lower summer flushing rates and higher residence time. In the current study, a seasonable variable was used in three models.…”
Section: Discussionmentioning
confidence: 73%
“…The influence of wind direction and lake-level change on microcystin concentrations is complex. Microcystis growth is favored during periods with high water stability; however, short wind-induced mixing events may have a positive effect on cyanobacterial growth by enhancing resuspension of nutrients (Bertani et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface area calculations were then compared to existing areal reports from Stumpf et al (2012) and Bertani et al (2017). Sandusky Bay was masked from the analysis due to HAB persistence within the bay throughout the season and its lack of spatial interaction with the western basin.…”
Section: Optically Classified Satellite Imagerymentioning
confidence: 99%
“…Spring phosphorus loading from the Maumee River has a significant influence on the size and severity of HABs in western Lake Erie (Bertani et al, 2017;Obenour et al, 2014;Stumpf et al, 2012), but this does not influence the spatial and temporal variability of the Detroit River and was not included as it was not in the scope of this research. To identify and determine which environmental variables have the greatest impact on the Detroit River plume and bloom and how these characteristics seasonally vary, a variety of meteorological, chemical, and physical parameters were considered (Table 2.1).…”
Section: Environmental Datamentioning
confidence: 99%